Teachers' Perceptions of Applying Contemporary Skill Acquisition Approaches in High School Physical Education - Millar, Sarah-Kate; Chow, Jia Yi; Gleeson, Mo; Cleaver, Michelle (Frontiers in Sports and Active Living, 2021)
Using contemporary skill acquisition approaches to skill learning appears to be a worthwhile pedagogical option for teachers and coaches in sports and Physical Education (PE). However, PE at the High School level in New Zealand has assessment components that are still underpinned by traditional and outdated skill learning theories. In response to this challenge, two motivated Heads of Department in PE undertook a department-wide professional development initiative to teach the national standard assessment via the use of a contemporary skill acquisition approach, which is student-centered, with an emphasis on enhancing exploratory learning and encouraging autonomy. Each department worked together over a 10-week period with a Higher Education specialist in skill acquisition to design and teach using contemporary skill acquisition approaches. Qualitative data was collected via semi-structured focus group interviews. Insightful data on the influence of teaching using contemporary skill acquisition approaches was acquired from the teachers in the two PE departments. It was found that substantial pedagogical practice changes were achieved by the teachers (e.g.. less focus on ideal technique and more on varying the context). They also enjoyed the learning experience that the contemporary skill acquisition approach offered as compared to their previous experience of more traditional teaching approaches, which have a focus on knowledge acquirement with few opportunities for exploratory learning. In addition, from a practical perspective, teachers were observed to demonstrate greater engagement in professional conversations around learning and could see greater relevance in the transfer of learning in the use of contemporary skill acquisition approaches to other teaching contexts.